The ethics primer for public administrators in government and nonprofit organizations - Svara, James H. (Burlington, MA : Jones & Bartlett Learning, 2022)
"The Ethics Primer for Government and Nonprofit Administrators is a concise introduction to the complex topic of administrative ethics that guides the student to align his or her own ethical commitments with the ethical standards of the field. Further, it helps the reader understand how to put these standards into practice as an individual administrator and as a leader of a public or nonprofit organization. Top 5 Problem-Oriented Features: 1. Grounds ethical behavior in key professional codes of ethics, especially the code of the American Society of Public Administration (ASPA). 2. Clearly articulates the duties and responsibilities of public servants through the framework of the "ethics triangle" which draws on universal ethical standards that stress virtue, principles, and promoting good outcomes. 3. Drawing on the author's research on the relationship of politics and administration, it describes the role of administrators as based on a complementary relationship with elected officials or members of organizational boards of directors. 4. Uniquely draws a distinction between universal ethical principles and the distinct duties of public administrators 5. Explores techniques for ethical analysis and problem solving including a model to guide application of the ethical triangle to resolving a specific issue The Ethics Primer is a concise introduction to the complex topic of administrative ethics that guides the student to align his or her own ethical commitments with the ethical standards of the field. Further, it helps the reader understand how to put these standards into practice as an individual administrator and as a leader of a public or nonprofit organization. To a greater extent than other texts, it grounds ethical behavior in key professional codes of ethics, especially the code of the American Society of Public Administration (ASPA). Codes articulate the duties and responsibilities of public servants. Duty is at the core of the "ethics triangle" that draws on universal ethical standards that stress virtue, principles, and promoting good outcomes"--
Introduction-and a pop quiz -- Administrative ethics : ideas, sources, and development -- Refining the sense of duty : responsibilities of public administrators and the issue of agency -- Reinforcing and enlarging duty : the philosophical bases of ethical behavior and the ethics triangle -- Codifying duty and ethical perspectives : professional codes of ethics -- Undermining duty : challenges to the ethical behavior of public administrators -- Overcoming challenges and deciding how to act responsibly : ethical analysis and problem solving -- Acting on duty in the face of uncertainty and risk : responsible whistleblowing -- Mandating duty : external measures to promote ethics -- Elevating ethical behavior in the organization -- Public affairs education and ethics -- Conclusion : the duties of public administrators.
Includes bibliographical references and index.
Keywords: Public administration -- Moral and ethical aspects; Nonprofit organizations -- Management -- Moral and ethical aspects